An Investigation on the Electrochemical Behavior and Antibacterial and Cytotoxic Activity of Nickel Trithiocyanurate Complexes - Ashrafi, Amir M; Kopel, Pavel; Richtera, Lukas (Materials (Basel, Switzerland), 2020)
The electrochemical redox behavior of three trinuclear Ni(II) complexes [Ni3(abb)3(H2O)3(µ-ttc)](ClO4)3 (1), [Ni3(tebb)3(H2O)3(µ-ttc)](ClO4)3·H2O (2), and [Ni3(pmdien)3(µ-ttc)](ClO4)3 (3), where abb = 1-(1H-benzimidazol-2-yl)-N-(1H-benzimidazol-2-ylmethyl)methan-amine, ttcH3 = trithiocyanuric acid, tebb = 2-[2-[2-(1H-benzimidazol-2-yl)ethylsulfanyl]ethyl]-1H-benzimidazole, and pmdien = N,N,N',N″,N″-pentamethyldiethylenetriamine is reported. Cyclic voltammetry (CV) was applied for the study of the electrochemical behavior of these compounds. The results confirmed the presence of ttc and nickel in oxidation state +2 in the synthesized complexes. Moreover, the antibacterial properties and cytotoxic activity of complex 3 was investigated. All the complexes show antibacterial activity against Staphylococcus aureus and Escherichia coli to different extents. The cytotoxic activity of complex 3 and ttcNa3 were studied on G-361, HOS, K-562, and MCF7 cancer cell lines. It was found out that complex 3 possesses the cytotoxic activity against the tested cell lines, whereas ttcNa3 did not show any cytotoxic activity.
Keywords: trimercaptotriazine; cyclic voltammetry; trithiocyanuric acid; nickel complexes